ICT acceptance among Malaysian urbanites: a study of additional variables in user acceptance of the new media - Ali Salman,; Mohd Azul Mohamed Salleh,; Mohd Yusof Hj. Abdullah,; Normah Mustaffa,; Abdul Latiff Ahmad,; Chang, Peng Kee; Suhana Saad, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
The dawn of the internet has brought about many implications to the already existing media and the way we communicate to one another and do things. Several scholars have conducted studies to understand the factors responsible for technology acceptance. The Technology Acceptance Model (TAM) is one of the much referred models for technology acceptance where perceived ease of use and perceived usefulness are recognised as the two main factors that influence computer usage behaviour. Subsequently, there have been several studies aiming at extending and modifying the TAM by proposing additional variables believed to contribute to technological innovation acceptance. This study aims at exploring and testing other factors that have not been explained by Technology Acceptance Model (TAM) in deteremining the acceptance of communication and information technology (ICT) by focussing on factors which may be unique to Malaysia. A survey was conducted to obtain the necessary primary data from 300 respondents in the Klang Valley, a metropolis consisting of the federal territory of Kuala Lumpur and the state of Selangor. Using SPSS 20.0., both desriptive and inferential statistical analysis were used to analyse the data. For the inferential statistics, multiple regressions were adopted to test the variables. The findings reveal that in the case of effects and influence on actual usage, beside the TAM’s perceived usefulness, additional variables, in particular, personal factors, communication channels and behavioural intentions have indeed contributed to the variations in the actual usage and acceptance of the internet. The findings thus have added more knowledge to the literature of technology acceptance while rendering practical implications to policy makers and technology providers, especially the new media, with regard to acceptance.